Dampak Kepemimpinan Transformasional dan Kepemimpinan Transaksional terhadap Kinerja Karyawan Bank BTN Cabang Madiun - Feliantiar, Okky David (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2017)
This study aimed to examine the effect of partially or simultaneously transactional leadership and transformational leadership on employee performance BTN Bank Branch Madiun. Total of samples is 80 people. The instrument of data collection using the questionnaire. Technique of data analysis in this research include hypothesis testing, regression analysis, and the coefficient of determination (R^2). The results of the analysis show that significant positive effect transactional leadership against the performance of employees in a Bank BTN branch of Madiun. Transformational leadership is a significant positive effect on performance of employees in a Bank BTN branch of Madiun. Transformational leadership and Transactional leadership are equally influential as well as significantly to the performance of employees in a Bank BTN branch of Madiun. Through the results of this research, expected management BTN Bank Branch Madiun to continue to maintain consistency in improving transactional leadership to employees, so that employees continue to be productive into work in the company.